Association of Organizational Culture with Creativity of Employees Regarding the Intermediation of Social Capital - Mahdi Zirak; Seyed Saeed Tabatabaee; Fatemeh Hoseini Dolatabadi (Tehran University of Medical Sciences, 2019)
Background and Aim: If organizational culture leads to stimulating organizational creativity, it will bring effectiveness and success to the organization. Therefore, the aim of this study was to determine the relationship between organizational culture and creativity of employees, taking into account the role of mediation of social capital in the development deputy of Mashhad university of medical sciences. Materials and Methods: This descriptive - analytical study was conducted in 183 employees of management development and resources department of Mashhad university of medical sciences that were randomly selected. The data collection tool was a standard organizational culture questionnaire (56 questions), employee creativity (60 questions), and social capital (28 questions). Data were analyzed using Structural Equation Modeling Method and with the help of the software Pls smart version two.  Results: There was a direct correlation between organizational culture and social capital (r=0.752) and between organizational culture and creativity of staff (r=0.464). Also, the social capital of the relationship between organizational culture and creativity of staff played the role of mediation. Conclusion: Organizations can help to increase creativity by agreeing on the values and beliefs in the organization and aligning individual and organizational goals, and planners cannot plan the criteria for increasing creativity of individuals regardless of organizational culture. If managers act to strengthen social capital, they can strengthen organizational culture in their organizations and create a suitable platform for creating a commonality.